Successful treatment of pyoderma gangrenosum after reducing mammoplasty: a case report - Gisela Hobson Pontes; Fernando Sergio Mendes-Carneiro-Filho; Luis Alejandro Vargas Guerrero (Revista Brasileira de Cirurgia Plástica)
Introduction: Pyoderma gangrenosum is a rare inflammatory disease characterized by the presence of ulcerated lesions. The etiology is unknown but apparently relates to immunological factors. The authors report a case of pyoderma gangrenosum in the postoperative period of a reduction mammoplasty, treatment, and the importance of early diagnosis to obtain a good aesthetic result. Methods: This is an 18-year-old patient who developed pyoderma gangrenosum after a reduction mammoplasty. The initial symptoms were the formation of violet blisters and ulcerated lesions in both breasts. The disease was suspected, and the patient was promptly treated with prednisolone. Cultures, biopsies and blood tests were performed. Hyperbaric therapy and nutritional support were performed. Daily dressings with epidermal growth factors were performed. After 60 days of follow-up, it was possible to achieve adequate wound healing and good aesthetic results. Results: Early diagnosis associated with systemic immunosuppressive therapy and rigorous local care were fundamental for disease stabilization. The association with hyperbaric therapy and nutritional support contributed to the lesion's epithelialization and the clinical picture control. The approximation of the wound edges with subdermal suture and the subsequent intradermal suture was possible due to the recovery of the dermis and stabilization of the disease. Conclusion: Early diagnosis of pyoderma gangrenosum is essential to achieve stabilization of the disease. It is possible to achieve good aesthetic results based on four elements: early systemic corticosteroids, daily local dressings with epidermal growth factor, nutritional support, and hyperbaric therapy.